1998
DOI: 10.1111/j.1471-6402.1998.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mediational Model Linking Self-Objectification, Body Shame, and Disordered Eating

Abstract: This study tests a mediational model of disordered eating derived from objectification theory (Fredrickson & Roberts, 1997). The model proposes that the emotion of body shame mediates the relationship between self‐objectification and disordered eating. Two samples of undergraduate women (n= 93, n= 111) completed self‐report questionnaires assessing self‐objectification, body shame, anorexic and bulimic symptoms, and dietary restraint. Findings in both samples supported the mediational model. Additionally, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
666
4
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 705 publications
(706 citation statements)
references
References 16 publications
30
666
4
6
Order By: Relevance
“…17,18 Moreover, objectification theory stresses that exposure to media with a strong focus on sexual attractiveness triggers a process of self-objectification, a perception of one' s own body that strongly emphasizes observable appearance and that is actively manifested by high levels of body surveillance. 19,20 Consistent with these theories, previous studies have indicated that adolescents' exposure to sexual content (offline and online) is related to more body surveillance and body image concerns and to less satisfaction with one' s sexual experiences. [5][6][7][8]21,22 In most studies, sex-related Internet use was operationalized as adolescents' use of sexually explicit Internet material (SEIM).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…17,18 Moreover, objectification theory stresses that exposure to media with a strong focus on sexual attractiveness triggers a process of self-objectification, a perception of one' s own body that strongly emphasizes observable appearance and that is actively manifested by high levels of body surveillance. 19,20 Consistent with these theories, previous studies have indicated that adolescents' exposure to sexual content (offline and online) is related to more body surveillance and body image concerns and to less satisfaction with one' s sexual experiences. [5][6][7][8]21,22 In most studies, sex-related Internet use was operationalized as adolescents' use of sexually explicit Internet material (SEIM).…”
mentioning
confidence: 78%
“…7,8,17,[19][20][21][22] Specifically, higher levels and/or faster increases in SEIM use predicted more body surveillance among boys and less satisfaction with sexual experiences among both boys and girls. Moreover, our study found that these effects extend to online behaviors other than SEIM use: sexual information seeking also predicted more body surveillance among boys and less satisfaction with sexual experiences among boys and girls.…”
Section: Discussionmentioning
confidence: 98%
“…Self-objectification (via body surveillance): whereas self-objectification involves a broad orientation to valuing appearance attributes over other personal characteristics (e.g., competence) [36,37], in line with prior objectification theory research [30,38,40,[47][48][49] we preferred to define it more narrowly as body surveillance [43,44]. Indeed, the literature has often equated body surveillance with self-objectification using these constructs interchangeably [32,34].…”
Section: Methodsmentioning
confidence: 99%
“…This sexual objectification is ubiquitous, occurring interpersonally across a variety of social interactions and mainly via media representations of female and male bodies that equate an individual's worth with the extent to which he/she fits the promoted standard of body size/shape [17,[27][28][29][30][31][32][35][36][37][38][39][40]. Although women and men may experience the cultural meaning of such objectification differently, both genders may encounter sexual objectification and the associated consequences [17,30,31,[38][39][40][41].…”
mentioning
confidence: 99%
“…previously discussed social physique anxiety) and have a detrimental impact on mental health, expressed, for example, in depression and eating disorders. Research has supported the central tenets of the objectification theory, linking body objectification in women directly to body shame, appearance anxiety, lack of psychological wellbeing and reduced self-esteem, decreased levels of intrinsic motivation and selfefficacy, and indirectly to eating pathology (Gapinski, Brownell, & LaFrance, 2003;Noll & Fredrickson, 1998;McKinley, 1999;Strelan, Mehaffey, & Tiggemann, 2003;Tiggemann & Slater, 2001). Furthermore, participation in sport or physical activity has been related to greater body shame (Parsons & Betz, 2001), which indicates either that participating in sport or physical activities may be one strategy females use to cope with their feelings of body shame, or that sport or physical activity may foster, or strengthen, pressure to live up to certain socio-cultural ideals of the body.…”
Section: Models and Measurement Of The Physical Selfmentioning
confidence: 99%